Traditional Learning Technologies and Ensuring the Quality of Economic Education in the Era of Digital Transformation - Y. V. Vertakova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2020)
The article considers the challenges of the Fourth Industrial Revolution and the resulting new requirements for the quality of education. There is an increase in the importance of information technologies in socio-economic processes, in particular in education. At the same time, the authors prove that the main thing in education is its result, not the educational technologies used. High-quality economic education requires the active use of not only new “fashion” technologies, but also traditional educational technologies.